EFFECTIVENESS OF PEPPERMINT-CITRUS AROMATHERAPY INHALERS IN REDUCING EMESIS GRAVIDARUM AMONG FIRST-TRIMESTER PREGNANT WOMEN - Wijayanti, Erna Eka; Qonitun, Umu; Hurin'in, Nur Maziyah; Khoir, Violetta Dity Virginia; Rahmawati5 , Eva Silviana (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: Aromatherapy is recognized as an effective, safe, and natural method for alleviating nausea-vomiting in pregnancy. The most prevalent physiological discomforts encountered during early gestation is nausea and vomiting of pregnancy (NVP), frequently termed "morning sickness." The manifestation of NVP is significantly influenced by fluctuating hormonal levels, particularly an elevation in Human Chorionic Gonadotropin (HCG).  This study aimed to analyze the impact of an inhaler stick combining peppermint and citrus aromatherapy on the frequency of these symptoms in first-trimester pregnant women. Method:  This was one-group pretest-posttest design utilized. The study included 28 first-trimester pregnant women, selected by simple random sampling. Participants used an aromatherapy inhaler stick containing 3 ml peppermint and 1 ml citrus, inhaled three times daily for 10 seconds per inhalation. Nausea-vomiting frequency was measured using the PUQE-24 questionnaire. Data analysis was performed using the Wilcoxon test. Result: The demographic analysis revealed that the largest age cohort comprised individuals aged 20–35 years (42.9%), while the majority of respondents were primigravida (42.9%). Regarding the intervention, a significant shift in symptom severity was observed. The Wilcoxon Signed-Rank Test analysis yielded a p-value of 0.000 (< 0.05), demonstrating a statistically significant impact of the peppermint and citrus aromatherapy inhaler stick on reducing the frequency of nausea and vomiting among first-trimester pregnant women. Conclusion : The use of aromatherapy inhaler sticks combining peppermint and citrus is successful in alleviating nausea and vomiting among women in early pregnancy. This aromatherapy technique offers a safe, natural, and easily applicable non-pharmacological alternative therapy.